ANALISIS PENERAPAN GOOD GOVERNANCE PADA PELAPORAN DAN PERTANGGUNGJAWABAN DANA DESA DI KECAMATAN PEUSANGAN KABUPATEN BIREUEN - Syarifah Rahmah; Indayani Indayani (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
The purpose of this research is to see how the village government and village communities apply the principles of village financial management in reporting and accountability of village funds, as the implementation of good governance in several villages in Peusangan District, Bireuen Regency. The method used in this research is descriptive qualitative using interviews. Interviews were conducted with parties from the District, representatives of the village community, and village government, such as the Keuchik, the Village Secretary, the Head of Financial Affairs, the Representative of the BPD (Village Consultative Body) / Tuha Peut. The results of this study indicate that the application of the principles of village financial management in reporting and accountability of village funds in Peusangan District, Bireuen Regency has been implemented, but not yet fully implemented to the maximum.